Prognostic Factors of Atypical Meningioma: Overall Survival Rate and Progression Free Survival Rate - Lee, Jae Ho (J Korean Neurosurg Soc, 2017)
OBJECTIVE: Atypical meningioma is rare tumor and there is no accurate guide line for optimal treatment. This retrospective study analyzed the prognostic factors, the effect of different methods of treatments and the behavior of atypical meningioma. METHODS: Thirty six patients were diagnosed as atypical meningioma, among 273 patients who were given a diagnosis of meningioma in the period of 2002 to 2015. Age, gender, tumor location, Ki 67, Simpson grade and treatment received were analyzed. We studied the correlation between these factors with recurrence, overall survival rate and progression free survival. RESULTS: Median overall survival time and progression free survival time are 60 and 53 (months). Better survival rate was observed for patients less than 50 years old but with no statistical significance (p=0.322). And patients with total resection compared with subtotal resection also showed better survival rate but no statistical significance (p=0.744). Patients with a tumor located in skull base compared with patients with a tumor located in brain convexity and parasagittal showed better progression free survival (p=0.048). Total resection is associated with longer progression-free survival than incomplete resection (p=0.018). CONCLUSION: We confirmed that Simpson grade was significant factor for statistically affect to progression free survival in univariate analysis. In case of skull base atypical tumor, it is analyzed that it has more recurrence than tumor located elsewhere. Overall survival was not affected statistically by patient age, gender, tumor location, Ki 67, Simpson grade and treatment received in this study.